2018
DOI: 10.4081/jphia.2018.798
|View full text |Cite
|
Sign up to set email alerts
|

Head trauma: A significant public health concern among young men in Botswana. Etiology referral patterns and opportunities for interventions

Abstract: This study aims to present and discuss acute Head Injury (HI) presentations including etiology, referral patterns and disposition in patients presenting to a major referral hospital in Gaborone, Botswana. Cross-sectional, retrospective data collection from July 2015 through September 2015 extracted descriptions of patient demographics, mechanism of injury, comorbidities, diagnosis and disposition from Emergency Centre (EC) records. 360 HI patients presented in three months, averaging four per day and increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…In this study, trauma was the leading cause of avoidable deaths. This nding is in keeping with previous studies conducted locally, showing trauma as the most common acute presentation and head injury as a signi cant public concern among young men in the country (12)(13)(14). Sixty-eight percent (68.2%) of road tra c collision (RTC) deaths in our country are considered preventable (15).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, trauma was the leading cause of avoidable deaths. This nding is in keeping with previous studies conducted locally, showing trauma as the most common acute presentation and head injury as a signi cant public concern among young men in the country (12)(13)(14). Sixty-eight percent (68.2%) of road tra c collision (RTC) deaths in our country are considered preventable (15).…”
Section: Discussionsupporting
confidence: 90%
“…An epidemiological review of emergency presentations to Botswana's largest referral hospital-Princess Marina Hospital (PMH)- in 2011 revealed that trauma was the second most common presenting problem in all age groups [ 7 ]. Trauma care in Botswana is currently inconsistent and not delivered in a systematic fashion and the country does not have a trauma registry or formal system for reporting trauma statistics in the health system [ 8 , 9 ]. Missing data variables and patient file unavailability are frequently encountered problems affecting trauma data retrieval [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma care in Botswana is currently inconsistent and not delivered in a systematic fashion and the country does not have a trauma registry or formal system for reporting trauma statistics in the health system [ 8 , 9 ]. Missing data variables and patient file unavailability are frequently encountered problems affecting trauma data retrieval [ [8] , [9] , [10] ]. Manually searching and retrieval of these paper-based patient files from the registry department is a daunting process.…”
Section: Introductionmentioning
confidence: 99%